Process for producing lithiated transition metal oxides

By intermingling transition metal precursors, lithium compounds, and potassium-containing additives and calcining at high temperatures, the process forms lithiated transition metal oxides with larger grain sizes, addressing the suboptimal performance and high costs of existing methods.

JP7669270B2Active Publication Date: 2025-04-28BASF CORPORATON
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021525209
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-11-09
Filing Date
2019-11-08
Publication Date
2025-04-28
Estimated Expiration
2039-11-08

AI Technical Summary

Technical Problem

Existing methods for forming electrochemically active materials, such as lithiated transition metal oxides, have not fully realized the theoretical capabilities of these materials, leading to suboptimal electrochemical performance and high manufacturing costs.

Method used

A process involving the intermingling of transition metal precursors, lithium compounds, and potassium-containing processing additives, followed by calcination in an oxidizing atmosphere at temperatures of 700°C or higher, to form lithiated transition metal oxides with larger primary particle sizes, typically 2 μm or greater.

Benefits of technology

This process improves the electrochemical capacity and reduces manufacturing costs by enhancing the grain size of the active material precursor, promoting better transport of active substances during calcination, and resulting in materials with reduced hardness for improved workability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669270000003
    Figure 0007669270000003
  • Figure 0007669270000004
    Figure 0007669270000004
  • Figure 0007669270000005
    Figure 0007669270000005
Patent Text Reader

Abstract

A process for forming electrochemically active materials, such as lithiated transition metal oxides, that overcomes previous problems related to throughput and calcination is provided, which process involves forming the material in the presence of a processing additive including potassium prior to calcination to produce an active material with increased primary particle grain size.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 62 / 757,875, filed November 9, 2018, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to the formation of electrochemically active materials suitable for use in primary or secondary batteries, and more particularly to the formation of lithiated transition metal oxides. [Background technology]

[0003] The formation of electrochemically active materials for use in batteries typically involves two major steps. First, a precursor is formed, such as by a co-precipitation reaction, whereby transition metals are intermixed in the form of hydroxides or carbonates to form a precursor powder. This precursor is then mixed with a lithium compound and calcined at high temperature to form the active material.

[0004] There is a strong desire to improve the electrochemical performance and reduce the manufacturing costs of the active materials formed in these processes. The performance of electrode materials for use in lithium-ion batteries is improved by reducing the particle size of the electrode material. This is generally due to three main advantages of small particle size. First, smaller particle size is believed to correlate with a larger surface area, resulting in improved charge transfer kinetics. Second, small particle size improves the diffusion kinetics of lithium ions into the interior of the particle, resulting in greater capacity at higher charge / discharge rates. Finally, smaller particles provide a larger effective contact surface with the electrolyte, increasing the possibility of lithium ion uptake from the electrolyte, improving the power density of the battery. Thus, attempts to reduce the particle size of active materials are an ongoing area of ​​research. Recent developments have allowed nanoscale particle sizes to be achieved.

[0005] Previous efforts to improve battery performance have been successful in many ways, but have not fully realized the full theoretical potential of these active materials. Thus, a need exists for improved processes for forming electrochemically active materials for use in electrochemical cells. Summary of the Invention

[0006] The following summary is provided to facilitate understanding of some of the innovative features unique to the present disclosure and is not intended to be a complete description, with the entire specification, claims, drawings, and abstract taken as a whole to provide a full understanding of the various aspects of the present disclosure.

[0007] A method is provided for improving the resulting electrochemical capacity of an electrochemically active material, such as a lithiated transition metal oxide. The process includes forming a lithiated transition metal oxide, including intermixing a transition metal precursor, a processing additive, and a lithium compound to form an active material precursor, and optionally heating the active material precursor to a temperature of 700° C. or higher in an oxidizing atmosphere for a calcination time sufficient to form a lithiated transition metal oxide having a plurality of primary particles with a grain size. Without being limited to one particular theory, improved transport of the active material in an oxidizing atmosphere is achieved by increasing the grain size of the active material precursor in combination with a processing additive, optionally forming a grain size within a predefined range, improving the overall resulting material. Optionally, a processing additive is added to the system prior to the first calcination. Optionally, the active material precursor is subjected to a first calcination (optionally prior to exposure to the processing additive), and the resulting particles are then intermixed with the processing additive to form a second lithiated transition metal oxide having a grain size larger than the first grain size achieved after the first calcination. The second lithiated transition metal precursor can then be subjected to a second calcination. The processing aid optionally includes potassium, optionally a potassium salt, optionally a carbonate or hydroxide of potassium. The processing additive can be present at 0.1 weight percent to 10 weight percent. In some embodiments, improved results can be achieved by forming particles having a grain size of 2 μm or greater, optionally 2 μm to 15 μm, and optionally 4 μm to 15 μm. In some embodiments, the molar ratio of lithium to transition metal in the active material precursor is 0.8 to 1.1. In some embodiments, the transition metal precursor optionally includes Ni, Co, Mn, Al, Mg, Ti, Zr, Nb, Hf, V, Cr, Sn, Cu, Mo, W, Fe, Si, B, other transition metals, or rare earth elements, or any combination thereof.The lithium compound is optionally lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium acetate, lithium peroxide, lithium bicarbonate, lithium halide, or combinations thereof. Optionally, the heating step is in an oxidizing atmosphere, optionally an oxygen-enriched or ozone-enriched atmosphere, where "enriched" is compared to the oxygen or ozone levels in the Earth's atmosphere at sea level. The heating step is optionally at a temperature between 700°C and 1000°C. The calcination time is optionally between 1 and 60 hours. The formed lithiated transition metal oxide resulting from the processes provided herein optionally has a crush strength of less than 40 Newtons. The lithiated transition metal oxide is optionally crushed and optionally pre-packed for subsequent use in an electrochemical cell or other desired use. [Brief description of the drawings]

[0008] The embodiments set forth in the drawings are illustrative and exemplary in nature and are not intended to limit the subject matter defined by the claims. The following detailed description of illustrative embodiments can be understood when read in conjunction with the following drawings. [Figure 1] 1 shows a schematic diagram of a process for forming lithiated transition metal oxides provided herein in accordance with some embodiments. [Figure 2A] 1 shows a scanning electron microscope image (5 μm scale) of LiNiO 2 particles formed in the absence of K 2 CO 3 processing additive and calcined, showing a relatively small primary particle grain size. [Figure 2B] 1 shows a scanning electron microscope image (5 μm scale) of LiNiO 2 particles formed in the presence of a K 2 CO 3 processing additive and calcined, showing a relatively large primary particle grain size. [Figure 3A] 1 shows a scanning electron microscope image (2.5 μm scale) of LiNi0.8Co0.1Mn0.1O2 particles formed in the absence of K2CO3 processing additive and calcined, showing a relatively small primary particle grain size. [Figure 3B]1 shows a scanning electron microscope image (2.5 μm scale) of LiNi0.8Co0.1Mn0.1O2 particles formed in the presence of K2CO3 processing additive and calcined, showing relatively large primary particle grain size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present disclosure relates to a new process for forming electrochemically active materials, optionally for use in electrochemical cells. Instead of focusing on the composition or structure of such active materials, the present invention reduces the time required to produce electrochemically active materials by reducing the sintering time and, in some embodiments, reducing the hardness of the material after sintering. It has been found that intentionally forming a relatively large primary particle size prior to sintering increases the throughput of the sintering reaction and improves material handling during sintering and downstream processes. Conventional methods for producing electrochemically active materials result in a final primary particle size of less than 500 nm. These small primary particle sizes are considered desirable for electrochemical performance. However, the present inventors have found that by increasing the size of the primary particles prior to final sintering, production time / cost can be reduced and performance improved. Thus, the processes of the present invention are in stark contradiction to conventional methods in that they result in relatively large grain sizes, in some cases on the order of 2 μm or more in diameter. It is these relatively large grain sizes of the material that are subjected to the sintering reaction.

[0010] Additionally, the provided processes address the need for cost reduction, at least through greater throughput and more efficient formation of electrochemically active materials. Manufacturing cost estimates suggest that the use of larger grain sizes as described herein in the manufacture of electrochemically active materials will result in significant cost reductions as compared to conventional processes.

[0011] As used herein, the term "lithiated transition metal oxide" refers to a metal oxide, optionally a mixed metal oxide, containing lithium and at least one transition metal, where the material has been subjected to calcination.

[0012] As used herein, the term "transition metal precursor" refers to a transition metal in the form of a hydroxide, oxide, oxyhydroxide, carbonate, or nitrate.

[0013] As used herein, the term "lithium compound" refers to lithium-containing compositions in the form of lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium acetate, lithium peroxide, lithium bicarbonate, or lithium halides.

[0014] As used herein, the term "active material precursor" refers to the intermixture product of a lithium compound, a transition metal precursor, and, in some embodiments, a processing additive provided herein.

[0015] As used herein, the term "calcination" is understood as a heat treatment in the presence of an oxidizing atmosphere to cause a chemical transformation of a material.

[0016] Temperatures provided herein are optionally either absolute as stated or approximate, defined as ±10° C. from the absolute as stated.

[0017] As used herein, "grain size" refers to discernible structures having an increased diameter (average cross-sectional dimension) compared to material produced in the absence of the processing additives provided herein, typically grain sizes of 0.5 micrometers (μm) or greater. Grain size is measured by microscope, such as a transmission electron microscope, and not by a standard particle size analyzer.

[0018] A process is provided for forming an electrochemically active material suitable for optionally reversibly inserting Li. Optionally, the electrochemically active material is a transition metal oxide, iron phosphate, titanate active material, LiMnO based with or without other elemental components, or LiCoO based with or without other elemental components. Illustrative examples of transition metal oxide electrochemically active materials include, but are not limited to, LiNiMO based chemistries, where M is any material and can be any transition metal, rare earth, or combination thereof. While much of this disclosure is directed to transition metal oxide electrochemically active materials, such as those that are primarily Ni on an atomic basis, it is understood that the process of increasing the grain size of the primary particles and calcining is applicable to other electrochemically active materials as well.

[0019] It has been found that by intermixing the processing additives containing potassium with the active material precursor, relatively large grain size primary particles can be obtained during the calcination reaction. Without being limited to one particular theory, it is believed that the larger grain size promotes improved transport of the oxidizing atmosphere or its components during calcination, thereby allowing the formation of a suitable end product with reduced calcination time. Furthermore, some embodiments of the process provided herein provide materials with reduced hardness compared to conventional methods, thereby improving subsequent processability for ultimate incorporation into electrodes or other suitable applications. Thus, in some embodiments, the process provided in the present disclosure includes intermixing a transition metal precursor, a lithium compound, and a processing additive to form an active material precursor, and heating the active material precursor to a temperature of 700° C. or more in an oxidizing atmosphere for a calcination time sufficient to form a lithiated transition metal oxide having a grain size of 0.5 mm or more primary particles. In some embodiments, the transition metal precursor and the lithium compound are first intermixed and subjected to a first calcination, and then the particles are intermixed with processing additives and subjected to a second calcination reaction to form a relatively larger primary particle grain size.

[0020] It is understood that the process includes forming an active material precursor prior to or simultaneously with the combination with the processing additive. The active material precursor is formed by intermixing a Li compound with a transition metal precursor. Optionally, the active material precursor is formed by intermixing a transition metal precursor with a Li compound in the absence of other materials or in the absence of processing additives. Optionally, the active material precursor is combined with the processing additive after being subjected to calcination. Alternatively, the processing additive is intermixed simultaneously with the transition metal precursor and the Li compound, whereby the Li compound and the transition metal precursor are optionally not significantly or intentionally intermixed prior to combination with the processing additive.

[0021] The lithium compound used herein is any suitable lithium compound known in the art for the formation of electrochemically active materials, optionally lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium acetate, lithium peroxide, lithium bicarbonate, lithium halide, or combinations thereof.

[0022] The lithium compound is intermixed with a transition metal precursor. The transition metal precursor can be formed by any method known in the art. In some embodiments, the transition metal precursor can be formed by a co-precipitation reaction, whereby a hydroxide, carbonate, nitrate, or other known suitable form of the transition metal is used to form a solution. By adjusting the pH of the solution, the transition metal precipitates to form the transition metal precursor.

[0023] The step of intermixing the transition metal precursor, lithium compound, and optionally processing additives can be carried out at a variety of temperatures, optionally from 0° C. to 100° C. or higher, optionally from 10° C. to 40° C. Intermixing can be carried out at any suitable pressure, optionally at about 1 atmosphere.

[0024] The transition metal can be any transition metal suitable for use in electrochemical cells. Examples of transition metals include, but are not limited to, Ni, Co, Mn, Al, Mg, Ti, Zr, Nb, Hf, V, Cr, Sn, Cu, Mo, W, Fe, Si, B, or other transition metals. Optionally, the transition metals used herein include or do not include rare earth metals. Optionally, rare earth metals are, among others, La, Nd, Y. In some embodiments, the transition metal precursor includes, but is not limited to, Ni, Mn, Co, Fe, or combinations thereof. In some embodiments, the transition metal precursor includes Ni.

[0025] In some embodiments, the transition metal precursor comprises Ni at an atomic percentage (at%) relative to other transition metals in the transition metal precursor of 10 at% or more, optionally 20 at% or more, optionally 30 at% or more, optionally 40 at% or more, optionally 50 at% or more, optionally 60 at% or more, optionally 70 at% or more, optionally 80 at% or more, optionally 90 at% or more, optionally 95 at% or more, optionally 96 at% or more, optionally 97 at% or more, optionally 98 at% or more, optionally 99 at% or more. Optionally, the atomic percentage of Ni is between 70 at% and 99 at% or more. Optionally, the atomic percentage of Ni is between 80 at% and 99 at% or more. Optionally, the atomic percentage of Ni is between 90 at% and 99 at% or more. Optionally, Ni is the only transition metal designed into or present in the material such that Ni is present at substantially 100 at%.

[0026] Optionally, the transition metal precursor comprises Ni and one or more other transition metals. The one or more other transition metals (other than Ni) are optionally each independently present at 0 at% to 90 at%, optionally 1 at% to 90 at%. Optionally, the one or more other transition metals are each independently present at 0 at% to 50 at%, optionally 1 at% to 50 at%. Optionally, the one or more other transition metals are each independently present at 1 at% to 30 at%, optionally 1 at% to 20 at%, optionally 1 at% to 10 at%, 1 at% to 7 at%, 1 at% to 5 at%, 2 at% to 20 at%, 5 at% to 20 at%, 10 at% to 20 at%. Optionally, one, two, three or more other transition metals other than Ni are present in the transition metal precursor.

[0027] An advantage of the process provided herein according to some embodiments is that raw precursor materials can be used, negating the requirement for highly purified or refined materials. For example, when nickel is used as the transition metal precursor, Ni can be mine grade. The transition metal precursor can be mine grade or can be further processed or refined.

[0028] The transition metal precursor is intermixed with the lithium compound and optionally processing additives to form the active material precursor. Intermixing is optionally performed to form a substantially homogenous material, thereby achieving excellent mixing of the materials and intimate contact between the Li compound and the transition metal precursor. A high shear mixer such as a Kawata Super Piccolo mixer or an Eirich mixer may be used. Any suitable mixing blade may be used, such as a pin type blade, a star type blade, or a microgranulation type blade. The tip speed of the blade correlates to the amount of shear or friction delivered to the material. The tip speed is optionally 5 to 30 meters per second (m / s), optionally 10 to 25 m / s.

[0029] The stoichiometric ratio of Li to the transition metal can be any suitable ratio, optionally 0.8 to 1.1, or any value or range therebetween. Optionally, the ratio of Li to the transition metal can be 0.9 to 1.1, optionally 0.95 to 1.1, optionally 0.95 to 1.05. For Ni-containing active material precursors, the stoichiometric ratio is measured as the ratio between Li and Ni in the material. The stoichiometric ratio of Li to the transition metal can be measured by any method known in the art. Illustratively, inductively coupled plasma atomic emission spectroscopy (ICP) or atomic absorption spectroscopy, optionally using standard methods described by J.R.Dean (Practical Inductively Coupled Plasma Spectroscopy, Chichester, England: Wiley, 2005, 65-87) and Welz and Sperling (Atomic Absorption Spectrometry, 3rd ed., Weinheim, Germany: Wiley VCH, 1999, 221-294). Illustratively, the chemical composition of each sample can be determined by a Varian Liberty 100 inductively coupled plasma (ICP) system.

[0030] In some embodiments, the process includes the formation of a first active material precursor having a plurality of primary particles having a first grain size. Thus, the active material precursor is formed according to conventional techniques and may therefore be defined by parameters such as granule size, porosity, density, etc., that are typical of such materials. Optionally, the first active material precursor is subjected to a calcination reaction to produce a first lithiated transition metal oxide having a plurality of primary particles having a first grain size. This first transition metal oxide is then optionally intermixed with a processing additive, and the resulting mixture is subjected to a second crystallization reaction to produce a second lithiated transition metal oxide having a plurality of primary particles having a second grain size that is larger than the first grain size.

[0031] The grain size may be determined using any known process, but is optionally obtained by microscopy. Optionally, the grain size can be obtained by sieving the material, scanning electron microscopy, transmission electron microscopy, or other suitable methods, for example, in embodiments where the grain size is too large for a standard particle size analyzer or the material is not suitable for analysis with a standard particle size analyzer. Optionally, the grain size is obtained using a particle analyzer, such as the SympaTec Helos particle size analyzer, which can measure particle sizes up to 8 millimeters (mm) or larger.

[0032] In the processes provided herein, the lithiated transition metal oxide is formed of a plurality of primary particles having a grain size of 0.5 micrometers (μm) or greater, the grain size being related to the diameter of a sphere using art-recognized methods. Optionally, the grain size is 0.5 μm to 15 μm, or any value or range therebetween. Optionally, the grain size is 2 μm to 15 μm. Optionally, the grain size is 4 μm to 15 μm. Optionally, the grain size is 0.5 μm or greater, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or greater. Optionally, the grain size is 0.5 μm to 10 μm, 0.5 μm to 9 μm, 0.5 μm to 8 μm, 0.5 μm to 7 μm, 0.5 μm to 6 μm, 0.5 μm to 5 μm, 0.5 μm to 4 μm, 1 μm to 15 μm, 1 μm to 10 μm, 1 μm to 9 μm, 1 μm to 8 μm, 1 μm to 7 μm, 1 μm to 6 μm, 1 μm to 5 μm. m, 2 μm to 15 μm, 2 μm to 10 μm, 2 μm to 9 μm, 2 μm to 8 μm, 2 μm to 7 μm, 2 μm to 6 μm, 2 μm to 4 μm, 2 μm to 4 μm, or 2 μm to 3 μm, 4 μm to 15 μm, 4 μm to 10 μm, 4 μm to 9 μm, 4 μm to 8 μm, 4 μm to 7 μm, 4 μm to 6 μm, or 4 μm to 5 μm.

[0033] The lithium transition metal oxide may optionally comprise a plurality of primary particles having a grain size of 2 μm or more, optionally 4 μm or more, and may be formed by combining an active material precursor or one or more transition metal precursors, a lithium compound, and one or more processing additives. The processing additive is a compound comprising potassium, optionally a potassium salt. In certain embodiments, the processing additive is a carbonate or hydroxide of potassium, illustratively K2CO3 or KOH. Optionally, the processing additive comprises KOH.

[0034] Processing additives are combined with other desired materials in the processes provided herein in weight percents of 0.1% to 10%, or any value or range therebetween, where the weight percent is relative to other materials in the total active material precursor. Optionally, the processing aid is present in a weight percentage of 0.1% to 20%, optionally 0.1% to 10%, optionally 0.1% to 8%, optionally 0.1% to 7%, optionally 0.1% to 5%, optionally 0.1% to 1%, optionally 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or more.

[0035] Processing aids may be combined with the active material precursor by simple addition, spraying, or other suitable methods.

[0036] The active material precursor, optionally its components, and one or more processing additives are intermixed to provide a coated or substantially uniformly mixed intermixed mixture. The formation of the active material precursor with the processing aids can be carried out in the same or different vessel as the step of intermixing the lithium compound with the transition metal precursor, or it can occur in the same vessel.

[0037] The resulting lithiated transition metal oxides provided herein optionally have a lower crush strength than compositionally identical materials formed by conventional methods without the processing aids provided herein. Crush strength can be measured by standard procedures recognized in the art. Optionally, the crush strength is less than 40 Newtons. Optionally, the crush strength is 40 Newtons or less, optionally 35 Newtons or less, optionally 30 Newtons or less, optionally 25 Newtons or less, optionally 20 Newtons or less, optionally 15 Newtons or less, optionally 10 Newtons or less, optionally 9 Newtons or less, optionally 8 Newtons or less, optionally 7 Newtons or less, optionally 6 Newtons or less, optionally 5 Newtons or less, optionally 4 Newtons or less, optionally 3 Newtons or less, and optionally. Newtons or less. Optionally, the crush strength is 60% or less, optionally 50% or less, optionally 40% or less, optionally 30% or less, compared to the crush strength of a compositionally identical material formed by conventional methods without the processing aids provided herein.

[0038] After forming the active material precursor, alone or in the presence of the processing additives provided herein, the resulting material is subjected to a solid-state reaction, such as calcination. Although a sagger can be used for the calcination process of the present disclosure, the calcination process is improved due to the reduced processing time to achieve the desired grain size of the resulting lithiated transition metal oxide. In addition to standard kilns and saggers, the material can be calcined in a fluidized bed calciner, a rotary kiln, a roller hearth kiln, or other such devices.

[0039] The calcination process is carried out at a calcination temperature and in an oxidizing atmosphere for a calcination time suitable for the formation of a lithiated transition metal oxide. The calcination temperature is optionally any temperature equal to or greater than 700 degrees Celsius (°C). The calcination temperature is optionally between 700°C and 1000°C or any value or range therebetween. Optionally, the calcination temperature is between 750°C and 950°C, optionally between 750°C and 900°C.

[0040] The firing time is optionally from 0.2 to 60 hours, or any value or range therebetween. Optionally, the firing time is from 0.2 to 50 hours, optionally from 1 to 50 hours, optionally from 1 to 60 hours, optionally from 10 to 50 hours, optionally from 10 to 20 hours. Optionally, the firing time is less than 60 hours, optionally less than 50 hours, optionally less than 40 hours, optionally less than 30 hours, optionally less than 25 hours, optionally less than 20 hours, optionally less than 15 hours, optionally less than 10 hours.

[0041] Calcination is performed in an atmosphere suitable for oxidizing the active material precursor. The atmosphere can contain a suitable amount or concentration of an oxidizing agent, optionally oxygen, ozone, or other suitable agent, optionally an oxidizing atmosphere in the form of an oxygen-enriched atmosphere, whereby the oxygen concentration is higher than in the ambient Earth air at sea level. Optionally, the atmosphere is air. The atmosphere is optionally provided at a suitable pressure, optionally about 1 atmosphere. The atmosphere is optionally in contact with the active material precursor at a flow rate to provide a desired number of atmosphere exchanges in the oven. The number of atmosphere exchanges per hour is optionally 3 to 150, optionally 3 to 100, optionally 5 to 150, optionally 5 to 100.

[0042] The resulting lithium transition metal oxide is optionally subjected to one or more post-calcination processes. In some embodiments, the lithium transition metal oxide is subjected to grinding, milling, or other processes to reduce the size of the aggregates or to pulverize the aggregates to improve downstream processing, to ensure homogeneity of the mixture and improve intermixing with binders, conductive compounds, or other materials suitable for forming an electrode.

[0043] The lithium transition metal oxides may be used in primary or secondary electrochemical cells. When used in primary electrochemical cells, the lithium transition metal oxides may be subjected to a pre-charging step, as recognized in the art, prior to incorporation into the primary cell.

[0044] Various aspects of the present invention are illustrated by the following non-limiting examples, which are intended for illustrative purposes and do not limit any practice of the present invention, and it will be understood that variations and modifications can be made without departing from the spirit and scope of the invention. EXAMPLES

[0045] Example 1: The active material precursor is formed using purified nickel hydroxide: 6.7 g of nickel hydroxide (described in U.S. Patents 6,432,580 and 6,444,363), 3.35 g of lithium hydroxide (LiOH*H2O), and 0.1 g of K2CO3 (2 wt.% (relative to nickel hydroxide)). The material is dry mixed for 20 minutes using a SPEX CETRIPREP 8000 mixer / miller to achieve homogeneity. As a control, a compositionally identical material is formed without the K2CO3.

[0046] The resulting active material precursor is subjected to calcination at 885° C. with flowing O at a flow rate of 21 SCFH (exchange rate of about 100). Calcination is carried out for 15 hours. Some of the resulting calcined granules are manually ground using a mortar and pestle and, optionally, pre-packed by standard techniques for downstream electrochemical analysis.

[0047] The particle topology of the materials formed in the absence or presence of K2CO3 is studied using corresponding micrographs shown in 2A and 2B, respectively, by SEM using a JEOL-JSM6320F scanning electron microscope (SEM, JEOL, Tokyo, Japan) equipped with energy dispersive spectroscopy (EDS). The primary particles of the lithiated transition metal oxides show relatively small primary particle grain sizes, with an average size after washing typically less than 3.6 μm. In contrast, when the active material precursor is formed in the presence of K2CO3 as a processing additive, the resulting primary particle grain sizes are typically on average 7.88 μm or larger.

[0048] The lithiated transition metal oxide material is ground and pre-packed according to standard procedures for subsequent electrochemical analysis. Electrochemical studies are performed in a half-cell configuration against a Hg / HgO reference electrode in 30% KOH solution. The lithiated transition metal oxide material is formed into a cathode powder for testing by mixing with Teflonized acetylene black (TAB-2) at 50% w / w and pressing onto a nickel screen. The cell is continuously discharged at a constant rate of 9 mA / g to -0.8 V against a Hg / HgO reference electrode. The capacity, particle size, and crush strength of the resulting material are shown in Table 1. [Table 1]

[0049] Example 2: LiNi 0.8 Co 0.1 Mn 0.1 The lithium cathode material was mixed with 5 grams of the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 is prepared by adding 1.4 grams of LiOH and 0.1 g of K2CO3 (2 wt. % (based on the mixed metal hydroxide)). A control material is formed similarly but without the presence of K2CO3. The material is mechanically mixed for 20 minutes using a SPEX CETRIPREP 8000 mixer / miller. The resulting powder mixture is then sintered at 850°C for 15 hours. The resulting lithiated composite material is then cooled to 25°C.

[0050] The particle topology of NCM811 materials formed in the absence or presence of K2CO3 is studied using the corresponding micrographs shown in 3A and 3B, respectively, by SEM using a JEOL-JSM6320F scanning electron microscope (SEM, JEOL, Tokyo, Japan) equipped with energy dispersive spectroscopy (EDS). The relative particle sizes are shown in Table 2. [Table 2]

[0051] For electrochemical analysis, the material obtained after calcination is ground in a mortar / pestle and pre-packed by standard techniques. The delithiated cathode material is studied for capacity levels and cycle life in CR2032 coin cells using lithium metal as the counter electrode. The lithiated composite is formed into cathode powder for testing by mixing with Timcal carbon Super65 (7.5 wt%), Timcal graphite KS10 (7.5 wt%), and 6 wt% PVDF (Kynar) binder. Anhydrous solvent (1-methyl-2 pyrrolidinone) was then added to the powder mixture to form a slurry. The slurry was then coated onto an aluminum substrate. The coating was dried at 85°C for several hours and calendared to a final thickness of approximately 60 μm. The cathode and anode materials are separated by a microporous polypropylene separator wetted with an electrolyte consisting of a 1 M solution of LiPF6 dissolved in a 1:1:1 volume mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) from Novolyte Corporation (MTI corporation). The cells were crimped and used to study the capacity and cycle life of the lithiated composites. The cell assembly and crimping were carried out in a glove box.

[0052] Cathode materials were tested at constant current charge and discharge (0.1C) to determine capacity and cycling performance using a Solatron 1470 Battery Test Unit and an Arbin Instruments battery testerpower system. The coin cells were charged and discharged at voltages between 4.3 V and 3.0 V. Cycling performance tests were performed at charge and discharge currents of 18 mA / g, respectively.

[0053] The foregoing description of the specific embodiment(s) is merely exemplary in nature and is in no way intended to limit the scope of the invention, its application, or use, which may of course vary. The present disclosure is provided in conjunction with non-limiting definitions and terminology contained herein. These definitions and terminology are not designed to serve as limitations on the scope or practice of the invention, but are presented for illustrative and explanatory purposes only. Although a process or composition is described as a sequence of individual steps or using specific materials, the steps or materials may be interchangeable such that the description of the invention may include multiple parts or steps arranged in many ways that are readily understood by those skilled in the art.

[0054] It will be understood that terms such as first, second, third, etc. may be used herein to describe various elements, components, regions, layers, and / or sections, but these elements, components, regions, layers, and / or sections should not be limited by these terms. These terms are used only to distinguish one element, component, region, layer, or section from another element, component, region, layer, or section. Thus, a "first element," "component," "region," "layer," or "section" discussed below could be referred to as a second (or other) element, component, region, layer, or section without departing from the teachings of this specification.

[0055] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used herein, the singular forms "a", "an" and "the" are intended to include the plural, including "at least one", unless the content clearly dictates otherwise. "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items. As used herein, it will be further understood that the terms "comprises" and / or "comprising", or "includes" and / or "including" specify the presence of the stated features, regions, integers, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, regions, integers, steps, operations, elements, components, and / or groups thereof. The term "or combinations thereof" means combinations including at least one of the aforementioned elements.

[0056] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs. Terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with their meaning in the context of the relevant art and this disclosure, and will not be interpreted in an ideal or overly formal sense unless expressly defined herein.

[0057] Various modifications of the invention in addition to those shown and described herein will be apparent to those skilled in the art. Such modifications are also intended to fall within the scope of the appended claims.

[0058] The patents, publications, and applications mentioned in this specification are indicative of the level of those skilled in the art to which this invention pertains, and are herein incorporated by reference to the same extent as if each individual patent, publication, or application was specifically and individually incorporated by reference.

[0059] The foregoing description illustrates certain embodiments of the present invention but is not meant to limit their practice.

Claims

1. 1. A process for forming lithiated transition metal oxide particles, comprising: mixing one or more transition metal precursors, a lithium compound, and a processing additive comprising a carbonate of potassium, excluding KOH, to form an active material precursor; heating the active material precursor to a temperature of 700° C. or greater in an oxidizing atmosphere for a calcination time sufficient to form lithiated transition metal oxide particles having a plurality of primary particles having a grain size of 2 μm or greater.

2. The process of claim 1, wherein the primary particles have a grain size of from 4 μm to 15 μm.

3. 3. The process of claim 1 or 2, further comprising mixing the lithiated transition metal oxide particles with a binder.

4. The process of claim 1 or 2, wherein the molar ratio of lithium to transition metal in the active material precursor is from 0.8 to 1.

1.

5. 3. The process of claim 1 or 2, wherein the processing additive is present at 0.1 weight percent to 10 weight percent.

6. 3. The process of claim 1 or 2, wherein the transition metal precursor comprises Ni, Co, Mn, Al, Mg, Ti, Zr, Nb, Hf, V, Cr, Sn, Cu, Mo, W, Fe, Si, Zn, B, other transition metals, rare earth elements, or combinations thereof.

7. 3. The process of claim 1 or 2, wherein the lithium compound is selected from the group consisting of lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium acetate, lithium peroxide, lithium bicarbonate, lithium halides, and combinations thereof.

8. 3. The process of claim 1 or 2, further comprising milling the lithiated transition metal oxide particles.

9. 3. The process of claim 1 or 2, wherein the heating step is in a fluidized bed calciner, a rotary kiln, or a roller hearth kiln.

10. 3. The process of claim 1 or 2, wherein the oxidizing atmosphere is an oxygen-enriched atmosphere.

11. 3. The process of claim 1 or 2, wherein the lithiated transition metal oxide particles have a crush strength of less than 40 Newtons.

12. The process of claim 1 or 2, wherein the temperature is between 700°C and 1000°C.

13. 3. The process of claim 1 or 2, wherein the time is from 0.2 to 60 hours.

14. 1. A process for forming a lithiated transition metal oxide comprising: intermixing a nickel-containing material with a lithium compound to form an active material precursor; heating the active material precursor in an oxidizing atmosphere at a temperature of 700° C. or greater for a period of time between 0.2 and 60 hours for a calcination time sufficient to form first lithiated transition metal oxide particles having a plurality of primary particles having a first grain size; intermixing the first lithiated transition metal oxide particles with a processing additive comprising potassium to form a second active material precursor; and heating the second active material precursor to a temperature of 700° C. or greater in an oxidizing atmosphere to form second lithiated transition metal oxide particles, whereby the plurality of primary particles have a second grain size, whereby the second grain size is greater than the first grain size, and the second lithiated transition metal oxide particles have a plurality of primary particles having a second grain size of 2 μm or greater.

15. The process of claim 14, wherein the second grain size is between 6 μm and 15 μm.

16. 16. The process of claim 14 or 15, wherein the nickel-containing material comprises nickel monoxide, nickel hydroxide, nickel oxyhydroxide, nickel trioxide, nickel carbonate, nickel nitrate, or any combination thereof.

17. 16. The process of claim 14 or 15, wherein the nickel-containing material further comprises Al, Co, Mn, or any combination thereof.

18. 16. The process of claim 14 or 15, wherein the lithium compound is selected from the group consisting of lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium acetate, lithium peroxide, lithium bicarbonate, lithium halides, and combinations thereof.

19. 16. The process of claim 14 or 15, wherein the processing additive is present at 0.5 to 5 weight percent of the active material precursor as a whole.

Citation Information

Patent Citations

  • Synthesis of Lithium Nickel Cobalt Dioxide

    JP2000515478A

  • Lithium complex metal oxide and nonaqueous electrolytic secondary battery

    JP2012109191A

  • Lithium-nickel-containing composite oxide and nonaqueous electrolyte secondary battery

    JP2017226576A

  • Lithium-nickel-containing composite oxide and method for producing same, and nonaqueous electrolyte secondary battery

    WO2017061633A1